Loan-to-Value Ratio and Housing Price Cycle: Empirical Evidence From Indonesia - Lim, Charvin; Nugraheni, Siwi (Universitas Muhammdaiyah Surakarta, 2017)
The subprime mortgage crisis in 2007-2009 which led to a global recession has highlighted the importance of regulating credit for housing market. The urgency arises not only to manage non-performing ratio, but further to manage price in the housing market which is a potent source of financial imbalance. Loan-to-value (LTV) regulation is imposed in order to dampen the housing price cycle, preventing the occurrence of bubble issue. This study tries to capture the influence of LTV implementation on housing price and assesses its effectiveness in the national scope. Error correction model is used to portray the short and long-term dynamics of housing cycle with regard to policy, macroeconomic, and financial variables. We concluded that LTV is an effective policy to dampen the price cycle in the long run, but not in the short run. In the short run, housing price is closely determined by the macroeconomic factors. Furthermore, we found that the implementation of LTV has made housing price to become more persistent, suggesting a change in the market expectation structure and the behavior of housing price cycle.